1994
DOI: 10.1111/j.1530-0277.1994.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity and Treatment of Alcohol Withdrawal in Elderly Versus Younger Patients

Abstract: We conducted a retrospective chart review of older (n = 48; mean age = 69) and younger (n = 36; mean age = 30) patients who were admitted to residential/inpatient treatment for alcohol withdrawal and dependence. Although the two age groups did not differ in terms of recent drinking history, the elderly group had significantly more withdrawal symptoms for a longer duration than the younger group. The elderly group also had more symptoms of cognitive impairment, daytime sleepiness, weakness, and high blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 11 publications
0
34
1
1
Order By: Relevance
“…Heavy, recent drinking would likely correlate with more sleep disturbance among alcoholic patients. Fourth, the severity of acute alcohol withdrawal, which can differ as a function of age (Brower et al, 1994), may be associated with worse sleep during subacute withdrawal (Gillin et al, 1990b). Because the severity of acute withdrawal was not measured in this study, no conclusions can be drawn regarding the association between withdrawal severity and impaired sleep in the alcoholic groups.…”
Section: Discussionmentioning
confidence: 92%
“…Heavy, recent drinking would likely correlate with more sleep disturbance among alcoholic patients. Fourth, the severity of acute alcohol withdrawal, which can differ as a function of age (Brower et al, 1994), may be associated with worse sleep during subacute withdrawal (Gillin et al, 1990b). Because the severity of acute withdrawal was not measured in this study, no conclusions can be drawn regarding the association between withdrawal severity and impaired sleep in the alcoholic groups.…”
Section: Discussionmentioning
confidence: 92%
“…Brower et al (1994) reported a more protracted and severe alcohol withdrawal syndrome in the elderly compared with younger people with equal drinking severity. However, a prospective study of admissions to a specialist detoxification unit did not find a relationship between the severity of alcohol withdrawal and age (Wetterling et al, 2001).…”
Section: Alcoholmentioning
confidence: 99%
“…Acute alcohol withdrawal syndrome is more pro tracted and severe in elderly people than in younger patients with drinking problems of equal severity (Brower et al, 1994). Outpatient detoxification may not be appropriate for older adults who are fragile, live alone with limited family support or who have multiple medical problems and prescribed medi cations (Liskow et al, 1989).…”
Section: Detoxificationmentioning
confidence: 99%